Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. (3rd July 2015) - Collison, Frederick T.; Xie, Yajing (Angela); Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R.; Fishman, Gerald A.; Allikmets, Rando
Abstract: Background : Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. Materials and Methods : An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. Results : Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. Conclusions : In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.